Animals in winter - Fisher, Ron frey50 (National Geographic Society usa, 1982)
Describes how animals face the rigors of winter by hibernating, migrating, storing food, or changing colors to blend with the winter landscape.
Keywords: Animals -- Wintring -- Juvenile literature; Animals -- Habits and behavior -- Juvenile literature